Jak w Czechosłowacji pojmowano filmy Munka i Wajdy, czyli film w kontekście zawikłanej historii - Hučková, Jadwiga; Hučko, Tomáš (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2017)
Films of Polish Film School, the most signifi cant formation in post-war history of Polish cinema, appeared in Czechoslovakia with several years of delay. Power feared that their message will be dangerous for spectators. Meanwhile – for viewers they remain unknown or diffi cult to understand and only a few critics and fi lm historians could read them in accordance with the intentions of the directors Andrzej Munk and Andrzej Wajda, being the main representatives of the stream.